Cytotoxic Extravasation: An Issue Disappearing or a Problem without Solution?. Issue 3 (May 2016) - Ferrari, Laura A.M.; Dinoi, Gabriella L.; Saibene, Gabriella; Re, Barbara; Balzarini, Augusta; Giordano, Lucia; Sala, Elena; Bregant, Cristina
Purpose: The incidence and management of antitumoral compound extravasation that occurred in our medical day hospital unit were registered in a 10-year period. Methods: A total of 114 episodes were consecutively recorded out of an estimated number of 211, 948 administrations performed (0.05%). Type of compound, localization, timing, symptoms, treatment, resolution, or sequelae were documented. Results: Extravasations after anthracyclines (17/114), platinum compounds (34/114), vinca alkaloids (7/114), and taxanes (34/114) were more frequently associated with edema and erythema ± pain. Five cases of monoclonal antibodies extravasation were observed without sequelae. With the involvement of an interdisciplinary task force and the use of dedicated guidelines, conservative management was successful in all patients. In the great majority of cases, recovery was complete within 48 hours after antidote administration. The support of our pharmacy was crucial. Physiatric evaluation was considered in several cases. No patients required surgery. Conclusions: We confirm that the adopted standardized approach to this event resulted in a satisfactory outcome and could be suggested as appropriate for managing extravasation in a large clinical context.